Rich unboxing experiences: complexity in product packaging and its influence upon product expectations. (11th September 2019) - Bae, Jieun; Self, James A.; Kim, Chajoong
We explore the influence of complexity in packaging design, defined as complexity of action and transformation, upon product appraisal at an unboxing phase of product life cycle. Three packaging designs of different complexity were developed and prototyped. Participant responses were then gathered through ten bipolar semantic differential scales that measured the influence of packaging complexity upon expectation towards and appraisal of the packaged product. Results indicate how increased complexity of action and transformation evoked higher expectations of product quality. Complexity of product packaging was shown to significantly influence the participants' appraisal of the packaged product's personality. Findings contribute to an understanding of how complexity in product packaging implicates the user's affective response to the packaged product through increased expectation resulting in either heightened delight or increased dissatisfaction. Implications for the use of complexity of action and transformation in product packaging design are discussed.